Force enhancement and force depression in a modified muscle model used for muscle activation prediction - Kosterina, N.; Wang, R.; Eriksson, A.; Gutierrez-Farewik, E. M. (Journal of Electromyography and Kinesiology, 2013)
This article introduces history-dependent effects in a skeletal muscle model applied to dynamic simulations of musculoskeletal system motion. Force depression and force enhancement induced by active muscle shortening and lengthening, respectively, represent muscle history effects. A muscle model depending on the preceding contractile events together with the current parameters was developed for OpenSim software, and applied in simulations of standing heel-raise and squat movements. Muscle activations were computed using joint kinematics and ground reaction forces recorded from the motion capture of seven individuals. In the muscle-actuated simulations, a modification was applied to the computed activation, and was compared to the measured electromyography data. For the studied movements, the history gives a small but visible effect to the muscular force trace, but some parameter values must be identified before the exact magnitude can be analysed. The muscle model modification improves the existing muscle models and gives a more accurate description of underlying forces and activations in musculoskeletal system movement simulations.